Editorial (diségno, 2017)
The first issue of a scientific journal is an important event, especially when it has been awaited for years: if it is true, as it is, that the UID Statute provides for a publication whose characteristics, according to current UID Regulations, which dedicate a specific chapter to this topic, are those of a proper scientific journal. It is true that in our area a great ferment occurred during the last decade, after a long period that saw only the activity of Disegnare. Idee, immagini, the only journal that has continued to publish uninterruptedly since its first issue, in 1989. In 2006, the online, open-access journal DisegnareCon, which regularly publishes two issues per year, was founded and immediately met with great success among ICAR/17 researchers, to the point of becoming the second journal for number of published articles, submitted to the VQR 2004-2010 (Evaluation of Research Quality) by researchers of the aforesaid disciplinary sector [...]